Answer:
1. Rewriting the expression 5.a.b.b.5.c.a.b.5.b using exponents we get:
5.
6.
7.
Step-by-step explanation:
Question 1:
We need to rewrite the expression using exponents
5.a.b.b.5.c.a.b.5.b
We will first combine the like terms
5.5.5.a.a.b.b.b.b.c
Now, if we have 5.5.5 we can write it in exponent as:
a.a as
b.b.b.b as:
So, our result will be:
Rewriting the expression 5.a.b.b.5.c.a.b.5.b using exponents we get:
Question:
Rewrite using positive exponent:
The rule used here will be: which states that if we need to make exponent positive, we will take it to the denominator.
Applying thee above rule for getting the answers:
5)
6)
7)
We know that so, we get
Step-by-step explanation:
Y=4(5)-9
=11
you must follow the formula given
Answer:
Step-by-step explanation:
We see that CF and DE are parallel to each other, which means that they had the same length with each other, so:
6n-1=5n+9
Subtract 5n for both side
6n-1-5n=5n+9-5n
n-1=9
Add 1 for both side
n-1+1=9+1
n=10
CF=
6n-1
=6(10)-1
=60-1
=59
DE=
5n+9
=5(10)+9
=50+9
=59
CD/FE:
4n+2
=4(10)+2
=42
True/False:
n=10 True
n=7 False
CF=59 True
FE=42 True
CD=30 False. As a result, n=10;CF=59; and FE=42 is your final answer. Hope it help!